A comparative study of oral health-related quality of life, depression, and periodontal health status of Turkish preclinical dental students - Fatih Karaaslan; Ahu Dikilitaş; Serife Esra Kurt (Wolters Kluwer Medknow Publications, 2020)
Background: The behavior of dental students, future professionals, toward their own oral health is not only a reflection of their understanding of the importance of disease prevention and improving the oral health of their patients but also affects their daily life and personal satisfaction. Through their undergraduate study, dental students develop and modify their attitudes toward their own oral health, which must improve if they are to serve as positive models for their patients. The aim of the present investigation was to compare the quality of life and associated factors, such as level of depression, with the periodontal and smoking status of preclinical (1st, 2nd, and 3rd year) dental students. Materials and Methods: The study consisted of periodontal assessment and a survey. The survey included demographic data, smoking status, Oral Health Impact Profile-14 (OHIP-14), and the Beck Depression Inventory (BDI). Results: No difference was observed between classes in terms of mean global OHIP-14 scores and BDI scores. The mean plaque index scores of 2nd year students were statistically higher than other students. The mean number of cigarettes smoked per day of 1st year students was significantly lower than other students. Conclusion: Current literature indicates that dental students have higher levels of depression, which correlates with higher smoking rates and lower oral health-related quality of life.